Urbánní dějiny a zelený prostor - Clark, Peter (Lidé města, 2010)
Czech urban historians discussed new research methods during lectures devoted to current trends in urban studies. Participants of the discussion included Donatella Calabi, Isabelle Backouche, Jaroslav Miller, and last, but not least, Peter Clark, who offered his lecture on green space in cities for publication. Appreciation of greenery in the city is presented as related to modernity, as such studied by urban historians only recently. The theme of the lecture is derived from the international project and book edited by Peter Clark and published by Ashgate in 2006.